SAT0034 Analysis of the t-cell subset composition in ankylosing spondylitis patients with long-standing anti-tnf therapy. (15th June 2017) - Dulic, S; Vásárhelyi, Z; Bajnok, A; Szalay, B; Toldi, G; Kovács, L; Balog, A
Abstract : Background: Ankylosing spondylitis (AS) is a chronic, progressive, immune-mediated inflammatory disease, driven primarily by Th1 and Th17 cells. Anti-TNF therapies are successfully used in AS to achieve and maintain remission. However, their influence on the composition of the T-cell repertoire is not clear, and, in particular, the few published studies involve mostly patients with anti-TNF treatment of short duration. Objectives: We aimed to characterize the changes in several T cell subsets after long-term anti-TNF treatment in AS patients. Methods: Twenty-two AS patients on long-term anti-TNF therapy were evaluated (15 anti-TNF-responders and 7 non-responders). A wide range of cell subtypes were analysed with flow cytometry and compared with therapy-naïve and short-term data. Results: Key findings include decreased proportions of naive CD4 and CD8 cells, increased frequencies of Th1 and Th17 cells and higher Th1/Th2 and Th17/Treg ratios in the long-term anti-TNF-treated patients (responders, non-responders and total), which was found to be significant not only when compared with healthy controls, but also with therapy-naive and short-term anti-TNF-treated AS patients. We have found several alterations within the various activated T-cell subsets – increase in CD4HLADR cells in responders, in CD8HLADR cells in the whole AS group and in responders, and in CD4CD25 cells in responders, and decrease in CD4CD69 cell percentages in long-term treated patients – becoming evident only after long-term anti-TNF-therapy. Conclusions: This study provides a comprehensive assessment of the impact of anti-TNF therapy on the T cell repertoire in AS, and indicate that these therapies induce profound changes within T-cells. Changes in T cell phenotype seem to develop progressively during therapy, even in inactive disease, and reflect an ongoing effector T-cell differentiation and activation, and a normalization of Treg development. Disclosure of Interest: None declared